Simulation of DMC Transesterification Reaction using ASPEN PLUS - Mohd Ali, Nur Amirah; Aziz, Norashid
Computer simulation has been widely used in chemical engineering processes and its implementation in biodiesel industry is very useful. In this study, a pilot plant scale of DMC transesterification reaction is simulated and validated using ASPEN PLUS software.